2012
DOI: 10.1007/s10544-011-9621-8
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic extraction and stretching of chromosomal DNA from single cell nuclei for DNA fluorescence in situ hybridization

Abstract: We have developed a novel method for genetic characterization of single cells by integrating microfluidic stretching of chromosomal DNA and fiber fluorescence in situ hybridization (FISH). In this method, individually isolated cell nuclei were immobilized in a microchannel. Chromosomal DNA was released from the nuclei and stretched by a pressure-driven flow. We analyzed and optimized flow conditions to generate a millimeter-long band of stretched DNA from each nucleus. Telomere fiber FISH was successfully perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Liu et al [19] performed FISH on centromere-sized cell arrays modified with 3-aminopropyltriethoxysilane (APTES) or polyethylene glycol (PEG)-coated glass slides with overnight hybridization. Wang et al [20] introduced an APTES-coated glass slide with a PDMS microfluidic for stretching chromosomal DNA from a single cell to perform FISH. In a recent study, a microfluidic consisting of a Pyrex-Si stack was generated and used for FISH to provide breast cancer prognosis [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [19] performed FISH on centromere-sized cell arrays modified with 3-aminopropyltriethoxysilane (APTES) or polyethylene glycol (PEG)-coated glass slides with overnight hybridization. Wang et al [20] introduced an APTES-coated glass slide with a PDMS microfluidic for stretching chromosomal DNA from a single cell to perform FISH. In a recent study, a microfluidic consisting of a Pyrex-Si stack was generated and used for FISH to provide breast cancer prognosis [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This technique could be extended to the use of microfluidics for dealing with material extracted from a single cell. 19 …”
Section: Discussionmentioning
confidence: 99%
“…The concept of stretching nucleic acids for analysis has been largely exploited in the case of bare DNA. Current techniques for DNA stretching comprise end-tethering, in combination with optical or magnetic tweezers, 67 stretching on polydimethylsiloxane (PDMS) stamps, 813 adsorption onto a modified surface under flow, 1415 shear flow, 1619 and nanoconfinement. 2021 While these techniques should be transposable to chromatin, we note that chromatin stretching is less studied, except for end-tethered stretching 2227 and a few recent nanoconfinement studies.…”
mentioning
confidence: 99%
“…The concept of aligning chromatin for high resolution imaging originated from naked DNA immobilization and stretching studies, which comprise of endtethering, in combination with optical or magnetic tweezers, stretching on polydimethylsiloxane (PDMS) stamps, adsorption onto a modified surface under flow, shear flow, and nanoconfinement. [28][29][30][31][32][33][34][35][36][37] Few methods have been demonstrated that allow the immobilization of isolated native chromatin molecules without disrupting their complex structure when imaged by TEM or AFM. 36 In order to facilitate high resolution imaging by EM, we developed a simple and robust method to immobilize and align isolated native chromatin on both continuous carbon coated TEM grids for positive staining EM and on holey grids for CryoEM, as shown in Figure 1, allowing finer details of chromatin to be visualized at nanoscale resolution.…”
Section: Nanomanipulation Of Chromatin On Em Gridsmentioning
confidence: 99%